Making TeleTalk a Healthy Competitor among the Mobile Phone Operators in Bangladesh (Journal of Business and Technology (Dhaka), 2012)
The people of Bangladesh are now dreaming of a digital Bangladesh. Fast development of telecommunications network is a must for the realization of the vision and aspiration of digital Bangladesh. Teletalk is the smallest in the six operator mobile phone market in Bangladesh having only 1.07 million subscribers and 2.04% market share. The present Teletalk is far away from its objectives, mission, and vision. Therefore, the main objective of this study is to analyse Teletalk and offer some suggestions to make it a healthy competitor among the mobile phone operators. The main strength of Teletalk is its domestic base and government ownership that encourages patriotic people to use TeleTalk. But bad network is its main weakness, and GP, Banglalink and Warid are the threats for Teletalk because of their size and quality of service. In order to become competitive in such a situation Teletalk should advertise its native nature more and apply direct selling policy along with strengthening the network coverage.DOI: http://dx.doi.org/10.3329/jbt.v5i2.9985Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 133-149